The Relationship Between Training Development Process And Employees - Abdul Rashid, Nurulizwa; Alzahrani, N. F.; Al-Shami, Samer Ali Hussein (J Fundam Appl Sci., 2018)
This research was conducted to examine the relationship human resource development based on training process and employees’ competencies. The majority of human resource in the developing countries are lacking behind and depend heavily on the outsourcing workers to fill up particular job vacancies. The existing of this problem differs from one country to another. For example, the development of human resource competencies in the Middle East region, especially Arab world still very low as reported by World Bank. A quantitative research method was conducted through a questionnaire with 152 of human resource managers in 152 corporations from construction sector. Based on the regression results, there is a positive association between human resource development process and employees’ competencies.